Description of a new Allobates (Anura, Dendrobatidae) from the eastern Andean piedmont, Venezuela - César Luis Barrio-Amorós (Phyllomedusa: Journal of Herpetology, 2009)
We describe a new nurse frog in the genus Allobates (Dendrobatidae) from Río Negro, Municipio Córdoba, Estado Táchira, in western Venezuela. This species is a leaflitter inhabitant of primary and secondary lowland rainforest at altitudes from 400 to 1000 m. The new species is similar to the species in the Allobates marchesianus group and is restricted to the slopes of the western Venezuelan Andes. It differs from its congeners by having an irregularly spotted dorsal pattern, diffuse oblique lateral stripe, ventrolateral stripe and yellowish belly on males.